CFD analysis of laminar axisymmetric diffuser flow. - Daniel Galvão Camilher (2009)
In this current work it is presented the two-dimensional axisymmetrical air flow simulations under laminar regime in a conical diffuser using Computer Fluid Dynamics (CFD). The use of diffusers in laminar flow can be seen in micro-pumps applications, especially for micro-electronics cooling. The objective is to analyze the static pressure recovery coefficient (Cp) for Reynolds 64, varying the diffuser expansion angle and the diffuser exit/entrance area ratio (A2/A1 = 1.5 and 2.0) for the cases with and without tail pipe. The diffuser geometric configurations and the Cp formulation are based in the current ESDU 73024 (Engineering Sciences Data Unit) publication. The partial differential equations system (Continuity and Navier-Stoke) was solved using a computer program based in the numerical Finite Element method. For diffusers without tail pipe (A2/A1 = 1.5 and 2.0), the Cp values under turbulent flow are higher than Cp values under laminar flow for the same expansion angles. For diffuser with tail pipe (A2/A1 = 1.5 and 2.0), the Cp values under turbulent flow are higher than Cp values under laminar flow up to 18 diffuser expansion angle. Above 18, the Cp for turbulent and laminar flow follow a similar trend. For diffuser (A2/A1 = 1.5 and 2.0) under turbulent flow with and without tail pipe, the Cp results were similar up to 10 diffuser expansion angle. Above 10, the diffusers with tail pipe presented Cp results higher than diffusers without tail pipe. The same occurs for diffuser (A2/A1 = 1.5 and 2.0) under laminar flow with and without tail pipe. Therefore, the finite element method showed a good agreement to solve this kind of problem and the results are important once static pressure recovery coefficient data for laminar flow is scarce in the literature.